Sexual Expression, Policies, and Practices in Skilled Nursing Settings Serving Older Adults: An Updated Assessment in the State of Kansas. (July 2022) - Jen, Sarah; Jeong, Mijin; Lafountain, Olivia; Doll, Gayle; Cornelison, Laci
Doll assessed sexual expressions, policies, and practices in Skilled Nursing Facilities (SNFs) in the state of Kansas. This study provided an updated and expanded assessment. A mixed-methods survey was distributed to administrators of all SNFs in the state of Kansas. Among 60 administrations, 84% reported any sexual expression among residents in their community within the past year and 55% reported expressions involving an individual with cognitive impairment. In response to sexual expressions, 70% of administrators believe staff would treat residents with dignity and respect and about 40% anticipated staff discomfort. About 40% of administrators reported having a policy related to sexual expression. Attitudes and responses of staff and administrators appear to be shifting in a sex-positive direction. While policies related to sexuality are more common than a decade ago, there is room for additional uptake, standardization, and infusion of person-centered language and practices.